1995
DOI: 10.1111/j.1570-7458.1995.tb01915.x
|View full text |Cite
|
Sign up to set email alerts
|

Variations in body length, weight, fat content and survival in Coccinella septempunctata at different hibernation sites

Abstract: Adults of Coccinella septempunctata L. (Coleoptera; Coccinellidae) were sampled in four overwintering sites: one in England and three at different altitudes in the Czech Republic (350–1420 m above sea level) in autumn 1992 and spring 1993. Body length, dry weight and fat weight were measured. There were significant differences in body length between sampling sites in spring 1993, but not in autumn 1992. The average sex ratio (♀) in all samples was 1:0.60 in 1992 and 1:0.72 in 1993. Females were significantly l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 18 publications
3
31
1
Order By: Relevance
“…A high proportion in the meadow of small individuals, less capable of long fl ight, indicated poor nutrition of larvae (and/ or pre -hibernation adults) and presence of local ladybirds. In this sample medium sized individuals had only 1.7% survival, while in the high altitude sample the survival was 83.3% in medium sized males and 86.7% in medium sized females (Zhou et al 1995, Hon ě k 1997. As the cause of mortality was not studied, it cannot be excluded that the high altitude hill top sample was less prone to fungal infection (Chapter 8.4.3 ) and this contributed to higher survival.…”
Section: Coccinella Septempunctata and O Ther S Pecies D Ormant In Thmentioning
confidence: 96%
See 2 more Smart Citations
“…A high proportion in the meadow of small individuals, less capable of long fl ight, indicated poor nutrition of larvae (and/ or pre -hibernation adults) and presence of local ladybirds. In this sample medium sized individuals had only 1.7% survival, while in the high altitude sample the survival was 83.3% in medium sized males and 86.7% in medium sized females (Zhou et al 1995, Hon ě k 1997. As the cause of mortality was not studied, it cannot be excluded that the high altitude hill top sample was less prone to fungal infection (Chapter 8.4.3 ) and this contributed to higher survival.…”
Section: Coccinella Septempunctata and O Ther S Pecies D Ormant In Thmentioning
confidence: 96%
“…Females, in which diapause was induced in the laboratory at 12L:12D and 18 ° C had 20% less lipids (0.164 mg). Zhou et al (1995) reported, also for the Czech Republic, a slightly higher content of fat in C. septempunctata females, sampled in mid -September in mountains (1420 m a.s.l. : 9.4 mg per individual) than in those from a hill (400 m a.s.l.…”
Section: Rate Of D Ecreasementioning
confidence: 99%
See 1 more Smart Citation
“…In several families within the order Lepidoptera, males contain greater fat reserves than females (Beenakkers et al, 1985). In most other species, females have greater fat reserves than males (Lease and Wolf, 2011;Nestel et al, 2005;Zhou et al, 1995). In species that use accumulated energy reserves obtained during their larval stages for reproduction, greater reserves would have a positive effect on fecundity because eggs have a high lipid content and therefore provide fitness advantages (Beenakkers et al, 1985;Downer and Matthews, 1976;Lease and Wolf, 2011).…”
Section: Fats and Fatty Acidsmentioning
confidence: 97%
“…Beetles can hibernate near their breeding sites: at forest edges, clearings, wind breaks, near isolated shrubs or can migrate to the hibernacula situated on the summits of prominent hills or mountains (Honek, 1989;Hodek et al, 1993;Hodek & Honek, 1996). Migrants and indi viduals remaining for winter in the proximity of breeding sites differ in some biological and ecological characters such as the intensity of diapause, duration of the dor mancy period, female/male ratio, fat reserves or mean body size (Hodek et al, 1977;Honek, 1989;Zhou et al, 1995). While relatively large, fatty and predominantly female individuals arrive at the prominent dormancy sites during August to hide among the stones or in grass tus socks, the smaller ones, staying at lower situations, can be found on plants even in October (Honek, 1989).…”
Section: Introductionmentioning
confidence: 99%